New PQ Controller for Interconnected Microgrids - Shahram Ramezani; Mohammad Ali Azimi (International Journal of Engineering and Management Research, 2020)
Distributed Generation Sources are becoming an inseparable part of modern electrical grids. Finding the control strategies which can help them to be as much as possibly beneficial for the grid has been a big concern among the researchers. In this work, a PQ controller for connecting A DC source simulates the effect of a Distributed Generation to the grid based on the decoupling of Active and Reactive powers has been proposed. The Simulation results which have been in the MATLAB/Simulink environment show the effectiveness of this control technique for injecting the defined value of active and reactive power to the grid.